Screening and identification of DNA aptamers toward Schistosoma japonicum eggs via SELEX - Long, Yuqian (Sci Rep, 2016)
Schistosomiasis is a major parasitic disease caused by blood flukes of the genus Schistosoma. Several million people all over the world are estimated to suffer from severe morbidity as a consequence of schistosomiasis. The worm’s eggs, which cause the symptoms of schistosomiasis, are generally used to diagnose the disease. In this study, we employed egg-based systematic evolution of ligands by exponential enrichment (egg-SELEX) and identified a panel of ssDNA aptamers specifically binding to eggs derived from S. japonicum. Among these, two aptamers LC6 and LC15 exhibited strong binding to and specific recognition of S. japonicum eggs, but not eggs from Fasciolopsis buski, Enterobius, Ascaris or Clonorchis sinensis. Furthermore, tissue imaging results revealed that LC15 could recognize S. japonicum eggs laid in liver tissues with a detection ratio of 80.5%. Collectively, therefore, we obtained useful aptamers specifically recognizing S. japonicum eggs, which will facilitate the development of an effective tool for both schistosomiasis diagnosis and drug delivery.